SOCIAL AND LEGAL CONDITIONALITY OF ESTABLISHING CRIMINAL LIABILITY FOR ENCROACHMENT ON THE FAMILY - Lychak, Volodymyr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of this article is to characterize the social and legal conditionality of the criminal law protection of the family. Methods: general and special methods of scientific cognition, in particular: comparative law, cognitive and analytical, structural and functional, formal and legal, hermeneutic, as well as analysis and synthesis methods have been deployed to achieve this purpose. The application of the above methods allowed to outline the issue of social and legal conditionality of criminal liability for encroachment on the family. Results: in Ukraine, the protection of the family has become more important than ever, as life in the context of full-scale military aggression of the Russian Federation against Ukraine has seriously affected family relations, the normal functioning of which depends on the stability of a number of legal, economic, social and political processes. In this article, the author demonstrated that the Ukrainian legislator had ensured the implementation of family protection, which is envisaged by the Constitution of Ukraine, laws of Ukraine, and numerous international legal enactments. Family protection in Ukraine is provided in many fields of law. In turn, one of the mandatory elements of a set of measures to protect the family is the criminalization of acts that infringe on the rights and legitimate interests of the family. Criminal offenses committed in the field of family relations negatively affect the further normal functioning of the family and its sustainable development, as well as the stable future of the state. By introducing norms into the Criminal Code of Ukraine that provide for criminal liability for criminal offenses against the family, the legislator did not violate the right to respect for family life guaranteed by the Convention for the Protection of Human Rights and Fundamental Freedoms, because there are family problems in life that cannot be solved without the help of public authorities. In addition, the growth of criminally illegal encroachments on the family indicates a lack of attention paid by the legislator to the implementation of the tasks proclaimed both in the Constitution of Ukraine and the laws of Ukraine, and in international legal acts tasks to protect the family, childhood, motherhood and fatherhood.